The effectiveness of employing digital games on First-Grade Students’ Achievement improving the academic achievement of first-grade students in mathematics and enhancing their motivation to learn: Qualitative Study from parents’ perspectives - Hamdan, Anan Shaker (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to explore the impact of employing digital games on improving first-grade students' achievement in mathematics and enhancing their motivation toward learning. A qualitative approach was employed, utilizing open-ended interviews with a purposive sample of seven parents from a public school. The interviews focused on understanding the effect of digital games on students' comprehension of basic mathematical concepts, such as addition and subtraction, as well as their role in motivating students and strengthening their engagement with the subject. The findings revealed that digital games significantly improved students' academic performance by providing an interactive and engaging educational environment, increasing their speed and confidence in solving mathematical problems. Additionally, the games played a pivotal role in motivating students through interactive challenges and rewards, fostering a positive attitude toward learning. The results also emphasized the importance of integrating digital games with teacher and parental support to achieve optimal educational outcomes. Furthermore, the study highlighted the need for enhancing game design by incorporating flexible levels to accommodate varying student abilities and addressing time-related challenges that might affect motivation. The study recommends improving the educational use of digital games to strengthen their effectiveness as a modern instructional tool in early primary education.
Keywords: Digital games; academic achievement; motivation; mathematics; primary education; interactive learning; game-based learning